Answer:
D. 25
Step-by-step explanation:
If this helps, please mark this as brainliest
Answer:
y+7=5/4(x-8)
Step-by-step explanation:
y-y1=m(x-x1)
y-(-7)=5/4(x-8)
y+7=5/4(x-8)
Answer:
B, C
Step-by-step explanation:
that's the answerrr
(1,-1)(2,2)
slope = (2 - (-1) / (2 - 1) = 3/1 = 3
y = mx + b
slope(m) = 3
use either of ur points...(2,2)...x = 2 and y = 2
now we sub and find b, the y int
2 = 3(2) + b
2 = 6 + b
2 - 6 = b
-4 = b
so ur equation is : y = 3x - 4
Answer:
4.5
Step-by-step explanation:
Just took the Test